Linguistic and content validity of the Swedish version of the PedsQL™ gastrointestinal symptoms scales and symptoms module for paediatric patients. (21st August 2021) - Bräutigam, Matilda; Dellenmark‐Blom, Michaela; Gatzinsky, Vladimir; Bergström, Jenny; Abrahamsson, Kate
Abstract: Aim: To describe the process of linguistic and content validity of the Swedish version of the PedsQL™ Gastrointestinal Symptoms Scales and Symptoms Module, measuring health‐related quality of life (HRQOL) in children with gastrointestinal (GI) disorders. Methods: The establishment of linguistic and content validity was carried out in compliance with international standards on patient‐reported outcome measurements. The process included forward translation, expert review and reconciliation, backward translation, backward translation review and interviews with 15 children aged 5–18 years with GI tract symptoms and 20 parents of children with GI tract symptoms aged 2–18 years. Results: The Swedish version of the PedsQL™ Gastrointestinal Symptoms Scales and Symptoms Module (child report 5–18 years, parent report for children 2–18 years) was achieved without major difficulties. Eight issues needed discussion after forward translation, and there was one change after backward translation and three revisions following patient and parent testing. Conclusion: A conceptually equivalent Swedish language version of PedsQL™ Gastrointestinal Symptoms Scale and Symptoms Module for children aged 2–18 years old was developed. This enables improved HRQOL evaluations in children with GI disorders in Sweden. Future research using a larger sample is recommended to evaluate validity and reliability of the Swedish language version of the module.